HUBUNGAN BAURAN PEMASARAN DAN KEPUTUSAN PEMBELIAN KONSUMEN TIKET BIS KRAMAT DJATI MELALUI AGEN TRAVEL DI BANGKALAN - Mohammad Tambrin (Kompetensi (Competence : Journal of Management Studies), 2014)
Globally, the role of travel agents in increasingly gaining importance in today’s travel and tourism industry. A travel industry without travel agents is quite unthinkable as it would result in utter chaos and disorder in the industry. The aim of this study is to investigate the relationship between the 4Ps, namely price, promotion, place and product, and customer decision-making over travel agents in Bangkalan. Travel agents are seriously considered for these 4Ps activities to ensure that they allocate their resources effectively and efficiently. A total of 75 respondents were selected from customers of two travel agents in Bangkalan. The data collected was analyzed using three statistical methods, that is, mean analysis, Pearson correlation and regression analysis. The results revealed that only product and price were associated with customer decision-making over travel agents. Based on the findings, strategic recommendations are proposed for the travel industry in Bangkalan.